Les archives vivantes des conservations foncières en Algérie - Didier Guignard (L’Année du Maghreb)
These collections contain copies of buying, saling or renting certificates for all properties which have been submited to french right from the xixth century. They were produced by Land Registries, as soon as their creation within the colony, but the institution works on after the independence despite the nationalizations. If european owners are overrepresented in these archives before 1962, they put some Algerians on stage as buyers, salesmen or hires out for properties depending on the french Law. Present context of privatisation gives back legal value to these documents that descendants of algerian owners during the colonial period – big or small ones – try to profit. So access to these archives is sensitive and uneasy – particularly to foreigners – but not forbidden. That’s a good new for the research because their state of conservation and their qualitative interest allow a great variety of subjects. They could contribute towards the renewal of economic and social history of Algeria during the xixth and xxth centuries.